Strategi Jurnal TV Sebagai Televisi Lokal Bersatelit Pertama di Provinsi Kalimantan Tengah Untuk Mempertahankan Eksistensi di Era Konvergensi Media - Hamiprojo, Michelle Serafim Princess Abigail; Kristama, Baswara Yua (LPPM Stikosa-AWS, 2024)
Local television is mass media that provides information in the form of regional cultural values and current issues that are not covered by national television. As a mass media, local television is also experiencing development with media convergence through the use of the internet and digitalization. One of the local television stations that has developed with this media convergence is Jurnal TV. This research aims to determine Jurnal TV's strategy as the first local satellite television in Central Kalimantan Province in the era of media convergence. This research is descriptive research with a qualitative approach with data obtained through interviews. Interviews were conducted with several informants who were internal to Jurnal TV. The interviews were analyzed qualitatively. The results explain that the strategies carried out by Jurnal TV can be classified into three, namely capital strategies by collaborating with regional beautification and provincial governments and the private sector as media partners and supported by program offers and advertising broadcasts for revenue. The next strategy is releasing Android and iOS-based applications to facilitate public access which is strengthened by the local characteristics of Jurnal TV. The final strategy is determining the target audience by classifying programs based on the age of the audience and involving the active role of the community to be involved in making the program.